The Influence Of High Performance Working Systems On Work Performance Effects Of Job Responsibility And Work Fatigue - Muhammad Naufal Khossy; Unggul Kustiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the effect of a high performance working system on work performance, the effects of job responsibility and work fatigue. Quantitative research using the Structural Equation Model (SEM) method, starting in 2023 by focusing on employees who have worked in companies that implement high performance systems and have worked for more than one year, then work in the Jabodetabek industrial area, and have supervisors. Data collection was carried out by distributing online questionnaires to 200 respondents. Data processing uses SmartPLS 3. The findings of this study indicate that a high performance working system (HPWS) can increase job responsibility. HPWS can also affect employee work fatigue with a large number of work targets that must be done. In addition, HPWS also affects work performance where employees with high performance will experience excessive fatigue due to work. The results of this research are expected to provide valuable insights for managers and company stakeholders in understanding the key elements that need to be considered in developing a high performance system. Keywords: High Performance Working System, Job Responsibility, Work Fatigue, Work Performance